A primary cavernous hemangioma of the thyroid gland: A case report and literature review. Issue 49 (December 2017) - Miao, Jie; Chen, Shubo; Li, Yongcai; Fu, Lin; Li, Hui
Abstract: Rationale: Thyroid hemangioma is benign and associated with fine-needle aspiration (FNA) biopsy or trauma in most cases. Its differential diagnosis is very difficult. Patient concerns: We presented the case of a 48-year-old man complained of slowly progressed swelling in the anterior neck for 20 years. Diagnoses: Ultrasound and CT scan revealed a hypoechogenic and heterogeneous mass measuring 4 × 3.5 cm located in the right lobe of thyroid gland. Postoperative pathological and immunohistochemical examinations of the surgical specimen revealed a primary hemangioma of the thyroid gland. Interventions: The patient received a right lobectomy of the thyroid. Outcomes: The patient had been followed up for 10 months after surgery without complications and remained asymptomatic. Lessons: Primary thyroid hemangioma should be considered when there is a well-circumscribed capsule mass on medical imaging without history of FNA or any other cervical procedures or trauma.